Observation of low turn-on field emission from nanocomposites of GO/TiO2 and RGO/TiO2. (January 2016) - Patil, Girish P.; Bagal, Vivekanand S.; Mahajan, Chetan R.; Chaudhari, Vijay R.; Suryawanshi, Sachin R.; More, Mahendra A.; Chavan, Padmakar G.
Abstract: Highly dense TiO2 nanotubes were synthesized by anodization of titanium foil. The TiO2 nanotubes were characterized by using XRD, FESEM, TEM and HRTEM. GO/TiO2 and RGO/TiO2 nanocomposites were synthesized by electrophoresis method using de-ionised water. FESEM images confirm complete covering of the GO and RGO nanosheets on the entire surface of TiO2 nanotubes. Field emission studies of TiO2 nanotubes, GO/TiO2 and RGO/TiO2 nanocomposites have been carried out. Turn-on field for the emission current density of 10 μA/cm 2, has been observed to be 2.9 V/μm, 3.3 V/μm and 2.6 V/μm for TiO2 nanotubes, GO/TiO2 and RGO/TiO2 nanocomposites respectively. For the TiO2 nanotubes, GO/TiO2 and RGO/TiO2 nanocomposites, the field enhancement factor (β) were calculated and are found to be 2059, 1482 and 2300. The turn-on field of the RGO/TiO2 nanocomposite has been found to be superior than other reported values of TiO2 nanostructures. To the best of our knowledge this is the first report on field emission studies of GO/TiO2 and RGO/TiO2 nanocomposites. Simple synthesis route coupled with the superior field emission behavior makes the present emitter more suitable for nano-electronics application. Highlights: Simple way of electrophoretic was employed for synthesis of nanocomposites. Low turn on field 2.6 V/μm for RGO/TiO2 nanocomposite has been found. Low turn on field attributed due to high enhancement factor. Stable nature of emission current has been found.